0

using the FITCH program and the FITCH derivation rules you should make a proof or derivation of C7 from P5 through P11.

P5: ∀x∀y(StrongPref(x,y)→ ¬StrongPref(y,x))

P6: ∀x∀y∀z((StrongPref(x,y)∧StrongPref(y,z))→StrongPref(x,z))

P7: ∀xIndiff(x,x)

P8: ∀x∀y(Indiff(x,y)→Indiff(y,x))

P9: ∀x∀y∀z((StrongPref(x,y)∧Indiff(y,z))→StrongPref(x,z))

P10: ∀x∀y(StrongPref(x,y)∨Indiff(x,y)∨StrongPref(y,x))

P11: ∀x∀y(WeakPref(x,y)↔(StrongPref(x,y)∨Indiff(x,y)))

C7: ∀x∀y∀z((StrongPref(x,y)∧StrongPref(y,z))→StrongPref(x,z))

C7 is totally the same as P6? So that means I can't use P6?

  • Yes C7 is the same as Premise6. – Mauro ALLEGRANZA Apr 7 at 10:22
  • 1
    Thus, assuming that the text of the problem is correct, you have a one-line only proof. – Mauro ALLEGRANZA Apr 7 at 11:59
  • Welcome to SE Philosophy! Thanks for your contribution. Please take a quick moment to take the tour or find help. You can perform searches here or seek additional clarification at the meta site. Don't forget, when someone has answered your question, you can click on the checkmark to reward the contributor. – J D Apr 7 at 16:30

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Browse other questions tagged or ask your own question.